Influences of moisture change and pore structure alteration on transport properties of concrete cover. (September 2021) - Yokoyama, Yuki; Nakarai, Kenichiro; Sakai, Yuya; Kishi, Toshiharu
Abstract: This study proposes a new method to analyze important factors that affect the air permeability of concrete cover. By conducting non-destructive tests on mockup box culvert specimens exposed to the outdoors (without rainfall), the changes in the moisture content, air permeability, and water absorption of concrete cover were investigated over a period of four years. Furthermore, the changes in their pore structure from 2.6 to 38 months were examined. The results clarified that the measured air permeability coefficient increased with age due to drying. Moreover, this study confirmed high correlation between the air permeability and total pore volume measured from the concrete after sufficient drying. Using the obtained equations, the influence of moisture change and pore-structure alteration on the air permeability coefficient were analyzed. This study reveals that their degree of influence is altered by the cement type and curing period.